Bioclimatic modeling of the European distribution of the invasive Asian tiger mosquito, Aedes (Stegomyia) albopictus (Skuse, 1895), with special reference to Ukraine - Kozynenko, I.I.; Tytar, V.M. (Доповіді НАН України, 2020)
Due to the spread of Aedes albopictus to many countries around the globe, which is an important mosquito vector
for the transmission of many viral pathogens and capable of hosting the Zika virus, it is important to determine the
potential suitable bioclimatic range in Ukraine. Bioclimatic modelling suggests that, under current climate conditions,
the vector species has varying chances in the near term to invade a number of regions in Ukraine, especially in the
south and west of the country: particularly, Crimea, the southern portion of the Odesa region, and Transcarpathian
one and, to a less extent, the Precarpathian region. Under the risk of invasion by the mosquito vector, are as well
coastal areas of the Black and Azov seas. Через поширення у багатьох країнах світу комарів виду Aedes albopictus, який є переносником низки вірусних збудників хвороб людини, у тому числі вірусу Зіка, є нагальна потреба визначити його потенційний біокліматичний ареал в Україні. На підставі результатів біокліматичного моделювання можна припустити, що за сучасних кліматичних умов цей переносник має різний шанс найближчим часом поширитися у низку регіонів України, особливо на півдні та заході країни: зокрема, Крим, південну частину
Одеської області та Закарпаття і меншою мірою Прикарпаття. Під загрозою інвазії з боку цього виду також знаходяться прибережні райони уздовж Чорного та Азовського морів. Из-за распространения во многих странах мира комаров вида Aedes albopictus, который является переносчиком ряда вирусных возбудителей болезней человека, в том числе вируса Зика, необходимо определить
его потенциальный биоклиматический ареал в Украине. На основании результатов биоклиматического
моделирования можно предположить, что в современных климатических условиях этот переносчик имеет
разные шансы в ближайшее время распространиться в ряд регионов Украины, особенно на юге и западе
страны: в частности, Крым, южную часть Одесской области и Закарпатья, и в меньшей степени Прикарпатья. Под угрозой инвазии со стороны этого вида также находятся прибрежные районы Черного и Азовского морей.